PENTINGNYA KETERANGAN SAKSI PADA TINGKAT PENYIDIKAN DALAM PERKARA KECELAKAAN LALU LINTAS DI WILAYAH POLISI RESOR KUTAI TIMUR - Devi Ariandi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTIONThe Significance of Witness Statement for Traffic Accident Investigation in Kutai Timur Police DepartmentWitness is a person who can give testimony which may be useful in an investigation or a case being heard in a Court about their firsthand account of something seen, heard, or experienced. However, a witness has a right to remain silent or their testimony would not to be considered based on KUHAP article 168.Investigation process plays a focal point to help determining the sequence and conclusion of traffic accident in Kutai Timur police department. The witness testimony or statement is a crucial part of the case, effectively helping investigator to close the case.Key Word: Witness, Witness Statement, Investigation, Traffic Accident